Mastite subclínica caprina: etiologia e diversidade microbiona do leite por sequenciamento do gene 16s RNAr - Bezerra, Andreia Batista (2016)
studies were developed with the objective of generating knowledge about the etiology of subclinical mastitis and the characterization of the microbiota profile of goats' milk associated with mastitis and the effects of infection on milk quality parameters. In the first chapter, we present a theoretical reference covering the etiology of subclinical mastitis and the advances in genomics related to the study of the goat milk microbiota. In the second chapter, the objective was identify the species causing intramammary infections in goats at different stages of lactation. For this, a total of 390 milk samples were collected from 65 half-bred dairy goats at six farms in semiarid Paraiba. Eighty-seven isolates were identified by mass spectrometry - time of flight (MALDI-TOF MS). The most common microorganisms associated with mastitis were coagulase negative Staphylococci (CNS), with higher frequencies observed for Staphylococcus caprae (13.6%), Staphylococcus chromogenes (7.6%), Staphylococcus epidermidis (5.1%), and Staphylococcus warneri (4.2%). In the third chapter, the objective was to determine the effect of subclinical intramammary infection caused by different pathogens on the production and quality of goat milk. For this, a longitudinal study was performed in 22 dairy goats (12 ¾ Alpine Goats and 10 Anglo Nubian) from a farm in the semiarid of Paraiba, Brazil. Milk from infected mammary glands showed decreased fat and total solids. In the fourd chapter, the objective was to characterize the microbiota profile of animals with and without mastitis by sequencing the V3-V5 region of the 16S RNAr gene, using amplification. The results of metagenomic through 16S rRNA gene sequencing reinforced not only the importance of the genus Staphylococcus spp. as the main cause of mastitis in goats but also revealed groups of microorganisms more abundant in milk without mastitis, such as the genus Nocardioides spp. and Ruminococcus spp.